Consistency Analysis of Port Industry Development and Chinese Economic Development - Sun Jianping; Li Zhenfu; Guan Yunxiao; Liu Tongchao (MATEC Web of Conferences, 2017)
As a function in organization and management, coordination is used to adjust the interrelation of the individuals in the organization in order to achieve the ultimate goal. Coordination can make individuals groups in a whole, reduce the contradiction and conflict between each other and promote the realization of the overall goal. The research on the coordination of relationship between the port industry of China and the growth of economy plays an important guiding role for the port industry and healthy development of national economy. According to the correlation model between port industry and economic growth, the correlation factor between port industry and economic growth is extracted, and the coordination indicator system of the relationship between the port industry and economic growth is established. Then, this article makes correlation analysis of the standardization of indicators, removes the bigger indicators of correlation coefficient and eliminates the impact of the duplication of information between indicators in order to simplify the indicator evaluation system. The actual results by data calculation show that there were six obvious changes in the coordination degree of the relationship between the port industry and economic growth in China during the period from 1990 to 2014.